2021
DOI: 10.3390/educsci11120801
|View full text |Cite
|
Sign up to set email alerts
|

From Cultural Heritage Preservation to Art Craft Education: A Study on Taiwan Traditional Lacquerware Art Preservation and Training

Abstract: In Taiwan, preservation and training policies of intangible cultural assets are highly valued by the government. In this study, lacquerware art craft education as intangible cultural heritage is the subject of this study. We conducted in-depth interviews and secondary data collection to obtain research data and carried out a grounded theory data analysis method through expert meetings to explore the passing on education strategy of “lacquerware art craft” in Taiwan. Firstly, based on Bloom’s educational object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…The authors investigated the current state of traditional lacquerware art preservation and training in Taiwan [5]. Using a combination of a literature review, expert interviews and field visits, in this study, several challenges for preservation and training were identified, including limited resources, difficulty transmitting traditional techniques, and declining interest in traditional arts and crafts.…”
Section: Contribution 3: From Cultural Heritage Preservation To Art C...mentioning
confidence: 99%
“…The authors investigated the current state of traditional lacquerware art preservation and training in Taiwan [5]. Using a combination of a literature review, expert interviews and field visits, in this study, several challenges for preservation and training were identified, including limited resources, difficulty transmitting traditional techniques, and declining interest in traditional arts and crafts.…”
Section: Contribution 3: From Cultural Heritage Preservation To Art C...mentioning
confidence: 99%
“…Open Coding, axial coding, dan selective coding digunakan dalam tiga proses berturutturut untuk menganalisis data (Hung et al, 2021;Xiang et al, 2021;Zhou et al, 2021). Pengumpulan data dan analisis data merupakan aktivitas yang saling terkait dalam grounded theory.…”
Section: Metodologiunclassified
“…Konsep yang ditemukan melalui rangkaian analisis data ini digunakan peneliti sebagai proses untuk memandu pengambilan data kembali. Terdapat tiga tahap pengkodean yang dilakukan secara berturut-turut untuk menganalisis data pada penelitian ini, diantaranya adalah Open Coding, axial coding, dan selective coding (Hung et al, 2021;Xiang et al, 2021;Zhou et al, 2021). Dalam proses analisis data, peneliti mengawali dengan pembuatan open coding, yaitu mengkodekan data-data untuk Menyusun tema-tema atau kategori-kategori tertentu.…”
Section: Metodologiunclassified